Analysis of Epidemiological and Evolutionary Characteristics of Seasonal Influenza Viruses in Shenzhen City from 2018 to 2024 - Weiyu Peng; Hui Liu; Xin Wang; Chao Li; Shunwu Huang; Shiyu Qi; Zhongnan Hu; Xiaoying Xu; Haihai Jiang; Jinyu Duan; Hui Chen; Manyu Huang; et al. (Viruses, 2025)
The SARS-CoV-2 pandemic and the implementation of associated non-pharmaceutical interventions (NPIs) profoundly altered the epidemiology of seasonal influenza viruses. To investigate these changes, we analyzed influenza-like illness samples in Shenzhen, China, across six influenza seasons spanning 2018 to 2024. Influenza activity declined markedly during the SARS-CoV-2 pandemic compared with the pre-pandemic period but returned to or even exceeded pre-pandemic levels in the post-pandemic era. Phylogenetic analysis of hemagglutinin (HA) and neuraminidase (NA) genes from 58 H1N1pdm09, 78 H3N2, and 97 B/Victoria isolates revealed substantial genetic divergence from the WHO-recommended vaccine strains. Notably, key mutations in the HA genes of H1N1pdm09, H3N2, and B/Victoria viruses were concentrated in the receptor-binding site (RBS) and adjacent antigenic sites. Hemagglutination inhibition (HI) assays demonstrated that most circulating viruses remained antigenically matched to their corresponding vaccine strains. However, significant antigenic drift was observed in H3N2 clade 3C.2a1b.1b viruses during the 2018–2019 season and in B/Victoria clade V1A.3a.2 viruses during the 2023–2024 season. These findings highlight the impact of NPIs and pandemic-related disruptions on influenza virus circulation and evolution, providing critical insights for future surveillance and public health preparedness.